AN ENGLISH SPEAKING TRAINING FOR THE DRAGON FRUIT PLANTATION WORKERS IN REMPANG ISLAND, BATAM: AGRO-TOURISM BASE - Ambalegin Ambalegin; Tomi Arianto; Nurma Dhona Handayani; Zia Hisni Mubarak (ASOSIASI IDEBAHASA KEPRI, 2022)
Batam is the third most visited city of foreign tourists due to the strategic location that closes to Singapore and Malaysia. It becomes a distinct advantage with the number of tourists visiting. In addition to marine tourism and shopping tourism, Batam has agro-tourism in the islands around Batam Island. Cafe Zore in Rempang Island's dragon fruit plantation is often visited by domestic and foreign tourists. Foreign tourists often experience difficulties in communicating with English because the employees could not speak English. It is aimed to develop employees' English skills through methods of community education and training with lecturing, discussion and demonstration techniques. The result of this training was the improvement of the English spoken ability. To sum up this PkM activity is that English communication skills are very important to welcome foreign tourists visiting and support the government to develop tourism in Batam